PENERAPAN AGYLE METHODOLOGY DALAM PENGEMBANGAN SISTEM INFORMASI GEOGRAFIS PEMETAAN DAERAH PERTAMBANGAN - Aji Seto Arifianto; Nugroho Setyo Wibowo (Jurusan Teknologi Informasi Politeknik Negeri Jember, 2019)
Indonesia is one country which has a wealth of natural resources in Asia's largest mine. Indonesian mining products are exported to many foreign countries and is able to produce a deficit for the country. So that natural resources mining Indonesia became one of the main commodities. The objectives of this study was to develop a geographic information system of the mining area is expected to provide an overview and information for stakeholders regarding mining areas in Indonesia. This system can provide convenience in data storage and geographic system application program can be accessed directly and can provide accurate data on the mining areas across Indonesia. The advantages of the system to be developed compared with the manual map is able t o update the information contained in it quickly and accurately as well as information in the form of digital maps. The development of geographic information system mapping mining areas is done by using Agyle Methodology. Results of this study include the design in the form of a global system in the form of Use Case Diagram, Class Diagram, Sequence Diagram, Collaboration Diagram, Activity Diagram, and Statechart Diagram and a geographic information system application program created using Microsoft Visual Basic.Net and MySQL as the database.